Street talk-2 : Slang used in popular American television shows (plus lingo used by teens, rappers, surfers!) - Burke, David (Word perfect., 2001)
Slang used in TV comedies(at the night club); More slang used in TV comedies (the new neighbors); Slang used in TV dramas(in the hospital)...